2022
DOI: 10.1007/s40519-022-01437-z
|View full text |Cite
|
Sign up to set email alerts
|

Craving for carbs: food craving and disordered eating in low-carb dieters and its association with intermittent fasting

Abstract: Studies point to positive outcomes in a diet with reduction of carbohydrates and that the associated practice of intermittent fasting (IF) might increase weight loss. Although dieting might be related to disordered eating, little evidence is available about the role of restrictive carbohydrates diets on disordered eating. This study aimed to explore if doing low-carb (LC) diets was related to disordered eating and if IF would increase these symptoms. The sample comprised university students ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…An example is question #3, “ I do not eat some foods because they make me fat ,” which was adapted to “ I do not eat some foods (source of carbohydrates) because they make me fat .” Low-carb dieters showed more remarkable cognitive restraint and more significant cognitive restriction of carbohydrates compared to non-dieters. Nevertheless, the overall score for cognitive restraint on carbohydrates correlated positively with guilt for food cravings in low-carb dieters 7 .…”
mentioning
confidence: 89%
“…An example is question #3, “ I do not eat some foods because they make me fat ,” which was adapted to “ I do not eat some foods (source of carbohydrates) because they make me fat .” Low-carb dieters showed more remarkable cognitive restraint and more significant cognitive restriction of carbohydrates compared to non-dieters. Nevertheless, the overall score for cognitive restraint on carbohydrates correlated positively with guilt for food cravings in low-carb dieters 7 .…”
mentioning
confidence: 89%
“…It is not worth to assume that a safe intervention will be effective for any individual. However, there will likely be an interaction between (i) eating history, (ii) cognitive-behavioral changes (such as disinhibition of eating behavior, increased fatphobic attitudes, intense food cravings, disconnection with internal signals, and changes in interoceptivity after many diets) [14][15][16] , and (iii) metabolic changes resulting from the length of time the individual follows the diet [16][17][18][19] .…”
Section: Implementation Of Ketogenic Dietsmentioning
confidence: 99%
“…Colombarolli et al investigated the role of a low-carbohydrate diet in food cravings. They found that a carbohydrate-restricted diet and intermittent fasting are related to increased rates of binge eating and food cravings compared to non-dieters [105]. However, these results were not confirmed in a recent randomized controlled trial (RCT) conducted in overweight or obese patients with T2DM, where no difference was reported between a low-fat, high-protein diet and a low-fat, high-carbohydrate isocaloric diet for a reduction in sweet cravings, fast-food cravings, and the Food Cravings Questionnaire-Trait (FCQ-T), for a similar loss of weight [106].…”
Section: Nutritional and Lifestyle Modifications To Improve Food Crav...mentioning
confidence: 99%